Circular Patch Antenna with Defected Ground for UWB Communication with WLAN Band Rejection - Jangid, K. G.; Tiwari, Ajay; Sharma, Vijay; Kulhar, V.S.; Saxena, V.K.; Bhatnagar, D. (Defence Science Journal, 2016)
The design and performance of coplanar waveguide fed modified circular patch antenna for possible application in ultra wideband communication systems with band rejection for upper wireless local area network band (5.15 GHz - 5.85 GHz) is reported. This antenna is designed on glass epoxy FR4 substrate having size 30 mm × 20 mm × 1.59 mm. The coplanar waveguide fed circular patch antenna is modified by introducing L shaped slits in ground plane and U shaped slot in patch and performance analysis of antenna is simulated by applying CST microwave studio simulation software. Different designed antennas were tested with available experimental facilities. The developed end product shows a nice matching with feed network at frequencies 2.62 GHz, 3.94 GHz and 8.50 GHz and provides 10.38 GHz (3.33 GHz - 13.71 GHz) impedance bandwidth with wireless local area network 5.5 GHz (4.74 GHz - 6.15 GHz) band rejection. The co and cross polar patterns in elevation and azimuth planes at two frequencies namely 2.62 GHz and 3.94 GHz are obtained which dictate that co-polar patterns are significantly better than cross polar patterns. The simulated peak gain of antenna is close to 3.86 dBi and gain variation with frequency shows a sharp gain decrease in the frequency range 4.74 GHz to 6.15 GHz.